Introduction to emergency management - Haddow, George D. (Butterworth-Heinemann, an imprint of Elsevier, 2014)
Introduction to Emergency Management, Fifth Edition, offers a fully up-to-date analysis of US emergency management principles. In addition to expanding coverage of risk management in a time of climate change and terrorism, Haddow, Bullock, and Coppola discuss the impact of new emergency management technologies, social media, and an increasing focus on recovery. They examine the effects of the 2012 election results and discuss FEMA's controversial National Flood Insurance Program (NFIP). Introduction to Emergency Management, Fifth Edition, gives instructors and students the best textbook content, instructor-support materials, and online resources to prepare future EM professionals for this demanding career.